Implementation of Active Learning Approach to Teach Biorisk Management and Dual-Use Research of Concern in Egypt. (June 2019) - Elhadidy, Mohamed; El-Tholoth, Mohamed; Brocard, Anne-Sophie
Introduction: Frequent reports of laboratory- and hospital-acquired infection in Egypt suggested a deficiency in handling hazardous samples and microorganisms among different researchers and professionals. The most common cause of laboratory incidents and potential exposure is often identified as a lack of biosafety training. Methods: In this study, we designed and implemented an effective laboratory biorisk management (BRM) training. Two workshops were delivered to 42 faculty members working in laboratories handling biological material in Egypt. The workshop modules were based on the global biorisk management curriculum developed by Sandia National Laboratories, with some modifications. The content was delivered to actively engaging participants in the learning process that included group work, case studies and scenarios, short presentations, demonstrations, hands-on activities, and questions and answers that created analytical thinking situations. These workshops introduced the concept of biorisk management, which combines risk assessment, risk mitigation, and performance systems and dual-use research of concern. Results: Results of pre-tests/post-tests revealed significant ( P < .001) improvement in knowledge acquisition among participants. Course evaluation surveys indicate that most participants felt that these teaching methods met their needs and that their personal laboratory practices would change as a result of the training course. Conclusion: We conclude that using varied hands-on strategies in teaching biorisk management provided the participants with the skills, tools, and confidence to guide their laboratory staff and colleagues on sustainable biorisk management to reduce the risks associated with infectious disease research in a laboratory setting.